2019
DOI: 10.1002/jso.25737
|View full text |Cite
|
Sign up to set email alerts
|

The role of double‐strand break repair, translesion synthesis, and interstrand crosslinks in colorectal cancer progression—clinicopathological data and survival

Abstract: Background and Objectives DNA repair is a new and important pathway that explains colorectal carcinogenesis. This study will evaluate the prognostic value of molecular modulation of double‐strand break repair (XRCC2 and XRCC5); DNA damage tolerance/translesion synthesis (POLH, POLK, and POLQ), and interstrand crosslink repair (DCLRE1A) in sporadic colorectal cancer (CRC). Methods Tumor specimens and matched healthy mucosal tissues from 47 patients with CRC who underwent surgery were assessed for gene expressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…However, there was less phospho‐γH2AX in the WT tissue than in the negative control (Figure 5A). Our results demonstrated that Boris enhances DNA repair under the treatment of AOM and DSS 23,24 . Therefore, 12 genes responsible for DNA damage repair were examined.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…However, there was less phospho‐γH2AX in the WT tissue than in the negative control (Figure 5A). Our results demonstrated that Boris enhances DNA repair under the treatment of AOM and DSS 23,24 . Therefore, 12 genes responsible for DNA damage repair were examined.…”
Section: Resultsmentioning
confidence: 79%
“…Our results demonstrated that Boris enhances DNA repair under the treatment of AOM and DSS. 23 , 24 Therefore, 12 genes responsible for DNA damage repair were examined. Three genes, MYC , BRCA1 , and POLH , were significantly downregulated after Boris knockout compared with the WT control (Figure 5B–E ).…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the inhibition of XRCC5 or XRCC6 improves the effectiveness of chemotherapy used in CRC, such as platinum-based drugs and/or radiotherapy. However, the downregulation of XRCC5 or XRCC6 is also associated with a poorer outcome of CRC; , one possible explanation is the intracellular localization of these proteins. In this regard, SW480 and SW620 cells manifest opposite responses to radiotherapy: the former is radioresistant and the latter is radiosensitive .…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer (CRC) is the third most common cancer in the world, and the proportion of women is slightly higher than that of men [ 1 ]. As with other types of cancer, mutations in certain genes, such as oncogenes and tumor suppressor genes, may contribute to the development of CRC [ 2 ]. CRC can be divided into sporadic, hereditary and familial based on the different pathways of mutations such as chromosomal instability (CIN), microsatellite instability (MSI) and CpG island methylation phenotype (CIMP) [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%